Epistemological beliefs of apprentices - Zinn, Bernd [Verfasser] (My University, 2013)
"Whereas the epistemological beliefs of learners of general subjects has been the focus of many studies in the past, so far, little is known about the beliefs of apprentices on knowledge and the acquiring of knowledge. The present study analysed the first level of epistemological beliefs of students in industrial and technical professions and their domain specificity. By means of an exploratory factor analysis, the five knowledge-related dimensions certainty of knowledge, structure of knowledge, application of knowledge, knowledge reasoning and source of knowledge were proven empirically for the surveyed apprentices (n=1002). The results of the study describe the level of epistemological beliefs of students and verify both the domain specific differences between the vocational fields of civil engineering, electrical engineering and mechanical engineering and the differences within those occupations." (Autorenreferat, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; Lehr-Lern-Forschung; Epistemologische Überzeugungen; Wissenserwerb; Auszubildender; Gewerblich-technischer Beruf; Empirische Untersuchung